Corporate glocalization strategy of Nongshim in America: The "pendulum theory" of globalized localization - Songmi Lee; Hyunjung Kim; Seungho Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
This study examines how Nongshim, a Korean instant noodle manufacturer, has expanded its operation globally within the concept of "open innovation" through its glocalization strategy, and how this strategy differs from the existing glocalization method enforced by global companies. The study shows how Nongshim used its unique glocalization strategy of "globalized localization", outlining the three stages by which the company switched its "glocalization focus", starting with "localizing", moving through "globalizing", then back to "localizing", while retaining its ultimate purpose of globalization. From the basis of the case analysis, the study proposes a "pendulum theory" that can be applied to local companies that are planning to expand their business in a global market.
Keywords: 650; case study; corporate glocalization; globalization; glocal strategy; instant noodles; Nongshim; open innovation; pendulum theory; US market